Tanggung Jawab KSEI Sebagai Lembaga Penyimpanan Dan Penyelesaian (LPP) dalam Bursa Efek Indonesia - Yuweni, Junita; Septiawanani, Rizka; Anisa, Rika (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2023)
This study aims to find out and explain how KSEI's responsibility as a depository and settlement institution in the Indonesia stock exchange. The method that the author used in this study was to use a qualitative descriptive method with a literature view. The results of the study stated that the storage and settlement institutions according to Law Number 8 of 1995 concerning Capital Securities Article 1 number 10 reads "Parties who carry out central custodial activities in stock exchange institutions". Currently, PT Kustodian Sentral Efek Indonesia (KSEI) has a license as an LPP that will carry out the storage function by resolving securities or violations that exist in the Indonesian capital market. KSEI plays an important role in the capital market, namely serving the securities management process, securities transaction settlement process and others. According to the PM Law Article 44 paragraph 1, the custodian carried out is in the form of responsibility to store securities owned by the account holder and has the condition of other obligations in accordance with the agreement between the custodian and the intended shareholder.